Study of the antioxidant effects of Eremostachys laciniata rhizome extracts in isolated rat hepatocytes - Haleh Vaez; Mojgan Arab; Abbas Delazar; Solmaz Asnaashari; Mohammad Ali Eghbal (Shiraz University of Medical Sciences, 2015)
Eremostachys laciniata, having rich flavonoid content, is expected to have a considerable antioxidant effect. In this study We used ACMS (Accelerated cytotoxic or protective mechanism screening technique) to evaluate the possible antioxidant effect of E. laciniata rhizome against oxidative cell damages induced by different types of oxidative stress such as iron-8-hydroxyquinolin (IQ) complex and copper in freshly isolated liver cells. The extracts were prepared with n-hexane, dichloromethane and methanol. Hepatocytes were isolated from male Sprague-Dawley rats by a two-step collagenase perfusion. Cell viability was measured by trypan blue exclusion method. DPPH (2, 2-diphenyl-1-picrylhydrazyl) assay was used to evaluate the antioxidant activity. ROS formation was measured by using DCFDA (2, 7-dichlorofluorescin diacetate) probe, mitochondrial membrane potential (MMP) was assessed by rhodamine 123 fluorescence and lipid peroxidation was determined by thiobarbituric acid reactive substances (TBARS) assay. The MET extract was demonstrated to possess a significant radical scavenging activity (RC50%=0.212). Unlike MET extract, the n-hexane and dichloromethane extracts showed toxic effects in cell suspensions. The MET extract significantly decreased cell death and ROS formation induced by IQ complex and copper and demonstrated protective effects against copper-induced mitochondrial membrane potential collapse and lipid peroxidation. The protection induced by MET extract can be attributed to antioxidant characteristics of the phenylethanoids content.